If ∫loga2 + x2dx = hx + C,

Previous Year Papers

Download Solved Question Papers Free for Offline Practice and view Solutions Online.

Test Series

Take Zigya Full and Sectional Test Series. Time it out for real assessment and get your results instantly.

Test Yourself

Practice and master your preparation for a specific topic or chapter. Check you scores at the end of the test.
Advertisement

 Multiple Choice QuestionsMultiple Choice Questions

981.

exx2 + 1x + 12dx is equal to

  • exx + 1 + C

  • - exx + 1 + C

  • exx - 1x + 1 + C

  • exx + 1x - 1 + C


982.

x + 1x1 + xexdx is equal to

  • log1 + xexxex + C

  • logxex1 + xex + C

  • logxex1 + xex + C

  • log1 + xex + C


983.

fxg'x - f'xgxfxgxloggx - logfxdx is equal to

  • loggxfx + C

  • 12loggxfx2 + C

  • gxfxloggxfx + C

  • loggxfx - gxfx + C


984.

0π4sinx + cosx3 + sin2xdx = ? 

  • 12log3

  • log2

  • log(3)

  • 14log3


Advertisement
985.

- 111 + x + x2 - 1 - x + x21 + x + x2 + 1 - x + x2dx = ?

  • 3π2

  • π2

  • 0

  • - 1


986.

If x3e5xdx = e5x54fx + C,then fx = ?

  • x35 - 3x252 + 6x53 - 654

  • 5x3 - 52x2 + 53x - 6

  • 53x3 - 15x2 + 30x - 6

  • 53x3 - 75x2 + 30x - 6


987.

xx2 + 2x + 22dx = ?

  • x2 + 2x2 +2x + 2 - 12tan-1x - 1 + C

  • x2 - 24x2 + 2x +2 - 12tan-1x +1 +C

  • x2 + 22x2 + 2x +2 - 12tan-1x +1 +C

  • 2x - 1x2 +2x +2 + 12tan-1x +1 +C


Advertisement

988.

If loga2 + x2dx = hx + C, then hx = ?

  • xloga2 +x2 + 2tan-1xa

  • x2loga2 +x2 +x +atan-1xa

  • xloga2 + x2 - 2x + 2atan-1xa

  • x2loga2 +x2 + 2x - a2tan-1xa


C.

xloga2 + x2 - 2x + 2atan-1xa

Let I = loga2 +x2dxBy using integration by parts, we get= loga2 +x2dx - d loga2 +x2dxdxdx + C= xloga2 +x2 - 2xx2 +a2dx +C= xloga2 +x2 - 2x + 2a2atan-1xa + C= xloga2 +x2 - 2x + 2atan-1xa +C hx = xloga2 +x2 - 2x + 2atan-1xa


Advertisement
Advertisement
989.

For x > 0, if logx5dx = ?xAlogx5 + Blogx4+Clogx3 + Dlogx2 +Elogx + F + Constant, thenA +B +C +D+E+ F = ?

  • - 44

  • - 42

  • - 40

  • - 36


990.

By the definition of the definite integral, the value of limn1n2 - 1 + 1n2 - 22 + ... 1n2 - n - 12 is equal to

  • π

  • π2

  • π4

  • π6


Advertisement